Representation of incapable or limited capable victim in criminal proceedings - Iemets, Ivan (Archives of Criminology and Forensic Sciences, 2024)
The article substantiates the thesis that insufficient scientific development characterizes the issue of representation in criminal proceedings of the interests of the victim, recognized by the court as incapable or partially capable. In this regard, the purpose of the article was to determine the specifics of representing the interests of an incapacitated and limited capable person in respect of whom a criminal offense was committed. It is established that the current criminal procedural legislation guarantees the right to participate in criminal proceedings initiated on the fact of violation of the rights of an incapacitated or limited capable person, and the legal representative of such a person, and a lawyer who will be entrusted with representing the interests of such a person. It is found that the principles of access to justice and equality of parties are fully implemented by the legislator in the context of representing the interests of victims of this group. After all, as a rule, in most cases they are guaranteed the right to apply for free legal services to the relevant centers and other institutions. It is determined that they can submit such an appeal independently, through a guardian or guardian. It is argued that the participation of a lawyer as a representative of the interests of an incapacitated or partially capable victim is a guarantee of the realization of his procedural interests, control over the activities of his legal representative, as well as the prevention of any violations by law enforcement agencies or entities that intend to counteract the investigation. This formulated a number of other scientifically based conclusions.